Prospect for the development of natural gas network and the multi-energy integration technology in pipeline networks - Weihe HUANG; Jing GONG (You-qi chuyun)
The natural gas pipeline network, as an important part of the natural gas industry and an indispensable participant in the energy Internet, plays a crucial role in the construction of China's energy industry and in the development of national economy. In this paper, the history of China's natural gas pipeline industry was reviewed from going through extreme hardships in the formative years of the new China after 1949 to leading the world in the construction and operation technologies of high-grade steel, large diameter, high pressure pipelines. And China's technological achievements in natural gas pipeline materials and equipment, design and construction, operation and maintenance were further systematically examined. Based on the current development trend of "One Pipeline Network" for natural gas pipelines and the future development mode of energy Internet, the importance of natural gas pipeline network in achieving the spatial and temporal balance between energy demand and supply by assisting the integrated development of multiple energies was identified under the background of achieving carbon peaking and carbon neutrality and energy transition goals; the role of the natural gas pipeline network was established in energy peak shaving, hydrogen blending transportation, energy conversion and storage. Moreover, the technologies of natural gas energy metering, energy storage and conversion facility construction, simulation of integrated natural gas pipeline network and power grid, and intelligent control of the natural gas pipeline network in energy Internet were systematically analyzed. As a result, this research serves as a valuable reference for determining the direction and ideas of natural gas pipeline network technology research in the context of energy Internet.